TEACHING WRITING DESCRIPTIVE TEXT USING PICTURE AND PICTURE METHOD THROUGH PADLET APPLICATION - Anita Anggraeni (PROJECT (Professional Journal of English Education), 2022)
The title of this research is “Teaching Writing Descriptive text  Using Picture and Picture Method through Padlet App”. The objectives of this research are to identify the  implementation of teaching writing Descriptive text  using Picture and Picture method through Padlet app and  to identify students’ and teacher’s obstacles in online learning. This research used descriptive qualitative method. The subject of this research was the tenth-grade students of one senior high school in Cimahi. Observation, questionnaire and  interview were used to collect the data. The result of the research indicated that the implementation of these method and media received positive response from the teacher and students in controlling students’ activities, make students confortable  take part in online learning, and meaningful. The students’ difficulties in writing using Picture and Picture method through Padlet are in applying language features and mechanics, require a lot of internet quota, difficult to focus, and a lot of plagiarism actions. The obstacles faced by the teacher in teaching online are related to technical issues such as students do not have devices and unstable student internet connection, teacher does not master technology, and difficulty in motivating students. Keywords:  Writing, Descriptive Text, Picture and Picture, Padlet